Performance of migrating birds optimization algorithm on continuous functions - (:unkn) unknown (Springer Verlag, 2014)
In this study, we evaluate the performance of a recently proposed metaheuristic on several well-known functions. The objective of this evaluation is to participate in a competition where several metaheuristics are compared. The metaheuristic we exploit is the recently proposed migrating birds optimization (MBO) algorithm. Our contribution in this study is to develop a novel neighbor generating function for MBO to be used in multidimensional continuous spaces. After a set of preliminary tests presenting the best performing values of the parameters, the results of computational experiments are given in 2, 10 and 30 dimensions. © Springer International Publishing Switzerland 2014.
Keywords: Continuous functions; Migrating birds optimization; Single objective optimization